Factors affecting women in acquiring leadership positions in workplaces: A human resource management perspective - Kelvin M Mwita; Eliza Mwakasangula (Universitas PGRI Madiun, 2023)
Under-representation of women in leadership positions in the corporate world has been a global concern. Scholars have explored many institutional barriers that women face in climbing the career ladder with limited studies assessing HR related factors. This study intended to assess HR related factors that affect women progressing to leadership positions in organizations, with specific reference to Tanzania. Guided by qualitative approach and human capital theory, the study involved semi-structured interviews to collect data from eight (8) respondents who were sampled by using a purposive sampling technique. The sample included female leaders and HR practitioners from seven (7) organizations in Tanzania. Thematic data analysis was employed. The study found that HR practices play a vital role in enhancing or limiting the number of female employees who reach leadership positions. The study recommends that organizations put in place fair and objective hiring systems that create fair grounds for both male and female employees. Training and development opportunities should be fairly distributed to both female and male employees with consideration that women play multiple leadership roles at home and at work as well. Organizations should consider employee promotion based on merit. Government, through its various agencies, should put in place measures that intend to control practices that discriminate against women, and hinder them from enjoying equal opportunities available at their workplaces.